2021
DOI: 10.1001/jamanetworkopen.2021.3287
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diagnosis and Triage in Validated Case Vignettes Among Nonphysicians Before and After Internet Search

Abstract: This survey study evaluates the factors associated with accurate diagnosis and triage by nonphysician adults who use the internet to find health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Users might also be more inclined to accept guiding advice from symptom checker apps before arriving at a health care facility. Interestingly, a web search seems to change only few people's urgency level [ 62 ]; this indicates a difference in advice-taking between symptom checker use and general web search.…”
Section: Discussionmentioning
confidence: 99%
“…Users might also be more inclined to accept guiding advice from symptom checker apps before arriving at a health care facility. Interestingly, a web search seems to change only few people's urgency level [ 62 ]; this indicates a difference in advice-taking between symptom checker use and general web search.…”
Section: Discussionmentioning
confidence: 99%
“…Building on prior related work [12, 22, 27, 36, 52, 53], we adopted a clinical vignette approach to measure the performance of Avey alongside several other checkers. A seminal work at Harvard Medical School has established the value of this approach [22, 52, 53] for testing checkers, especially that it has been also a common method to test physicians on their diagnosis abilities [53].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in Australia, around 80% of people search the Internet for health information, and nearly 40% seek guidance online for self-treatment [13, 27]. In the US, almost two-thirds of adults search the Web for health information and roughly one-third utilize it for self-diagnosis , trying to discover by themselves the underlying causes of their health symptoms [36]. A recent study showed that half of the patients investigated their symptoms on search engines before visiting emergency departments [38, 51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety percent of databases used to create the DermAssist software extracted images from patients with lighter skin. 2 Melanoma Project, the largest available pigmented lesion dataset, relies heavily on images collected from patients with fair skin from the United Kingdom, United States, and Australia. 3 Given the skewed ethnic and geographic variability of the datasets, AI may proffer less accurate diagnoses for conditions encountered in patients with darker skin, such as acral melanoma or nail melanoma.…”
mentioning
confidence: 99%